Administration of advanced development areas and free ports of the Russian Federation. - A. Kostyukov (Правоприменение, 2017)
УДК 242.9The subject. In the article the problems of creation and development of advanced development areas and free ports are analyzed. Territories with a special regime for the conduct of business are a phenomenon long known to the world. Classic examples: the island of Delos (Greece) was declared a free trade zone, where merchants were exempt from taxes, duties and certain administrative duties. In Russia, the modern history of territories with a special regime for the implementation of entrepreneurial activity begins in the 1990s, when the first free economic zones were created: Vyborg, Dauria, Kuzbass, Nakhodka, Sadko, Sakhalin, TechnopolisZelenograd, Yantar, free trade zones or free customs zones Sheremetyevo, Moscow Franco-Port, Franco-Port Terminal. It is necessary to use the positive experience of foreign countries in this field.The purpose of this paper is to describe the problems of managing the territories of advanced development and free ports and to offer the government of the Russian Federation effective ways of solving these.Methodology. The author uses a dialectical method, a method of analysis and synthesis, a formal legal method, a comparative legal method.Results, scope. The author criticizes the Russian system of administration of the territories of advanced development and free ports of Vladivostok. The author points out that since each territory of advanced development and free ports of Vladivostok territory operate simultaneously on the territory of several municipalities, it is obvious that the highest exeutive authority of the subject of the Russian Federation, specifically the highest official of the subject of the Russian Federation in whose territory the сorresponding territory of advanced development. The author also proposes to extend the legal regime of the territories of advanced development and free ports to entities located in the territory of Western and Eastern Siberia. Effective organizational interaction between state and municipal authorities, the Management Company, the Supervisory and Public Councils with entrepreneurs and investors can only be ensured through the use of such a function of the authorities as coordination.Together, these measures will minimize the existing gap in the standard of living of the population and imbalance in the economic development of regions throughout Russia, and ultimately entail the accelerated economic development of the Russian Federation as a whole.The results of the study can be applied in the design of the legal regulation of creation and development of territories of advanced development and free ports.Conclusions. The author comes to the conclusion that the highest executive authority of the subject of the Russian Federation, specifically the highest official of the subject of the Russian Federation (the governor) should become the coordinating center of administration of territory of advanced development and free ports of Vladivostok. This approach will improve the business and investment climate in all (and not in the selected) constituent entities of the Russian Federation, create prerequisites for the development of their economic potential, will allow the subjects of the Russian Federation to make the most of their competitive advantages.